RELASI KUASA TOKOH LAKI-LAKI DAN PEREMPUAN DALAM NOVEL GARIS PEREMPUAN KARYA SANIE B. KUNCORO - Ery Agus Kurnianto (Kantor Bahasa Provinsi Gorontalo, 2017)
The issue of power between men and women in the construction of patriarchal culture becomes very interesting. Women become parties repressed by the power of men because of the cultural construction formed by men. One of the media that can be used by women to resist construction is literary work. The object of this research is a novel entitled Garis Perempuan by Sanie B. Kuncoro. Within the concept of structuralism, the writer aims to identify the behavior, mindset, and myths concerning women that are represented in the novel. The writer uses gender and representation theory to identify the representation of women. The method used in this paper is descriptive-analytic with an objective approach. The objective approach by analyzing intrinsic elements based on the empirical facts contained in the work. The result shows that women are represented as colonized and feminist.